Constrained intensification in Algerian Arid Zones: Systemic evaluation of agricultural development programs in Laghouat Province - Moulai, Adel; Bouammar, Boualem (Journal of Aridland Agriculture, 2026)
Algerian agricultural development programs (Access to Agricultural Land Ownership - APFA and Land Development through Concession - MVTC) in arid regions aimed to expand agricultural production and create employment, but their economic efficiency remained poorly quantified. This study evaluated the economic performance and intensification modalities of agricultural development programs in the steppe zones of Laghouat province through a systemic analysis of farms. A stratified survey was conducted among 90 active farms distributed across three agroecological zones (Atlas Mountain Foothills, High Steppe Plains, Saharan Plateau). Data were analyzed using hierarchical cluster analysis, ANOVA, and discriminant analysis to identify production systems and evaluate their economic efficiency. Five distinct production systems emerged from the classificatory analysis: small diversified farms (9.2 ha, $5,065/year), mixed crop-livestock farms (31.4 ha, $16,900/year), large mechanized cereal farms (174 ha, $31,371/year), very small diversified farms (5.8 ha, $2,677/year), and arboricultural farms (1 ha, $708/year). The overall capital efficiency ratio was 1.84, with significant territorial variations (F=3.58, p=0.032). Quantitative expansion reached +78% of agricultural area, but qualitative intensification remained limited with yields often below national averages. The development programs generated marked differentiation of production systems according to local agroecological constraints. Decision-makers must adopt differentiated territorial approaches integrating agropastoral specificities to optimize the efficiency of public investments in arid zones.